2014
DOI: 10.1016/b978-0-444-62619-6.00023-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding alcohol use disorders with neuroelectrophysiology

Abstract: Neurocognitive deficits associated with impairments in various brain regions and neural circuitries, particularly involving frontal lobes, have been associated with chronic alcoholism, as well as with a predisposition to develop alcohol use and related disorders (AUDs). AUD is a multifactorial disorder caused by complex interactions between behavioral, genetic, and environmental liabilities. Neuroelectrophysiological techniques are instrumental in understanding brain and behavior relationships and have also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 301 publications
(361 reference statements)
6
76
0
Order By: Relevance
“…This may suggest the presence of some compensatory mechanism (e.g., sensorimotor beta; attention-related alpha) that prevents behavioral slips even when prefrontal response conflict processes are lacking, that other cognitive control-related processes important to optimal task performance are relatively intact in the presence of decreased conflict-related theta, or that EEG correlates of response conflict/cognitive control may be more closely associated with adolescent drinking than performance-based measures. In addition, despite the finding that theta dynamics were significantly related to drinking only during response conflict trials, given the lack of association between AAU and behavioral performance, it is possible that individual differences in other more global cognitive states that may affect EEG characteristics, such as wakefulness or general vigilance (Rangaswamy and Porjesz, 2014; Clayton et al, 2015), may have contributed to the observed effects. Further work is needed to tease apart the relationship between adolescent drinking and the various subdomains (e.g., sustained attention, conflict processing) of cognitive control.…”
Section: Discussionmentioning
confidence: 90%
“…This may suggest the presence of some compensatory mechanism (e.g., sensorimotor beta; attention-related alpha) that prevents behavioral slips even when prefrontal response conflict processes are lacking, that other cognitive control-related processes important to optimal task performance are relatively intact in the presence of decreased conflict-related theta, or that EEG correlates of response conflict/cognitive control may be more closely associated with adolescent drinking than performance-based measures. In addition, despite the finding that theta dynamics were significantly related to drinking only during response conflict trials, given the lack of association between AAU and behavioral performance, it is possible that individual differences in other more global cognitive states that may affect EEG characteristics, such as wakefulness or general vigilance (Rangaswamy and Porjesz, 2014; Clayton et al, 2015), may have contributed to the observed effects. Further work is needed to tease apart the relationship between adolescent drinking and the various subdomains (e.g., sustained attention, conflict processing) of cognitive control.…”
Section: Discussionmentioning
confidence: 90%
“…While there have been no studies evaluating genotype influences on sleep EEG, the data from wake EEG studies are clearly relevant, especially the known association between the GABA gene GABRA2 and beta oscillations (Porjesz et al 2002) and between the cholinergic gene CHRM2 and delta oscillations (Porjesz and Rangaswamy 2007; Rangaswamy and Porjesz 2013). It should be noted however that EEG during wakefulness that is measured in association with cognitive or behavioral tasks, reflects the activity in task specific pathways and networks, whereas sleep EEG is measuring a baseline state.…”
Section: 0 Familial Predisposition For Alcoholism Effects On Sleep?mentioning
confidence: 99%
“…ERO measures have been used as effective tools to understand brain mechanisms underlying alcoholism and its predisposition (for reviews, see Porjesz et al, 2005; Pandey et al, 2012; Rangaswamy and Porjesz, 2014; Kamarajan and Porjesz, 2015). Further, as reported in the combined analyses of ERP and ERO data, ERO measures yielded additional information than the traditional ERP measures to discriminate alcoholics from controls (e.g., Jones et al, 2006b) as well as high-risk from low-risk individuals (e.g., Rangaswamy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Collaborative Study on the Genetics of Alcoholism (COGA), we have successfully used EROs as endophenotypes in the search for genes involved in alcoholism and related disorders (for reviews, see Porjesz et al, 2005; Pandey et al, 2012; Rangaswamy and Porjesz, 2014). Genetic studies of the theta ERO phenotype in a visual oddball task has been associated with several genes, including CHRM2 (Jones et al, 2004; Jones et al, 2006a), GRM8 (Chen et al, 2009), and HTR7 (Zlojutro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%